Mining, Paternalism and the Spread of Education in the Congo since 1920 - Dacil Juif (African Economic History Network (AEHN), 2019)
This study adds the case of a Belgian colony to a literature that has mainly focused on differences in school enrollment between French and British African territories. While most studies emphasize the supply- side, especially the constraints on missionary activity, we highlight the role of demand from the colonial mining industry. We use various primary sources to assess quantitatively and qualitatively the development of school enrollment in the Congo since 1920. We show that the regional inequality in education that crystallized in colonial times persisted decades after independence. The provincial disparities are used as a point of departure to explain how the mining industry worked as a catalyst for the expansion of primary school enrolment. The paternalistic policy of "stabilization", i.e. of permanent settlement of workers and their families near the work sites, introduced by the Union Mini\~AƒÂre du Haut Katanga as well as by most concessionary companies in the Belgian Congo in the mid-1920s, went hand in hand with high investments in primary schooling. The aim of the industry was to save expenses on recruitment and European labour, and to make investments in miners' and their children's education profitable.
Keywords: N27; N37; N47; N57; N97; 330; Education; colonial Africa; the Congo; regional inequality